Designing a Digital Business Study Program using Lean Startup Methodology - Zabenaso Queen; Aneira Anjani; Anggy Giri Prawiyog (Startupreneur Business Digital (SABDA Journal), 2024)
In the ever growing digital era, the need for adaptive and innovative business education is becoming increasingly important. This research focuses on the central problem of the lack of integration between traditional business theory and dynamic digital business practices, as well as the need to develop entrepreneurial skills that are relevant to today's market. The aim of this research is to design a digital business study program that utilizes the Lean Startup methodology to promote action-oriented and experimental learning. The method used in this research is a participatory curriculum design approach, involving stakeholders from academia, industry and digital entrepreneurs. Data is collected through surveys, in-depth interviews, and case studies, which are then analyzed to identify best practices and principles of effective learning. The conclusion of this research shows that the integration of Lean Startup in digital business study programs can increase students' adaptability and innovation capabilities, preparing them for success in a rapidly changing business environment. The designed program emphasizes iterative learning, rapid market validation, and scalable business model development, all of which are crucial for modern entrepreneurship. This research provides a framework for more responsive and practical digital business education, which can be adopted by educational institutions to develop curricula that meet current and future industry demands.